Environmental affects on teamwork: case study of a trauma and surgical intensive care unit - Montgomery-Colbert, Debora A., author; Gilley, Jerry, advisor; Burns, Patrick, committee member; Makela, Carole, committee member; Banning, Jim, committee member (Colorado State University. Libraries, 2010)
The research was conducted to identify how the physical environment shapes teamwork with regards to communications and role assignments in a Trauma and Surgical Intensive Care Unit (TSICU). The site was selected due to my personal experience with the trauma team and the environment. Ten team members included in the study consisted of personnel from facilities, emergency room staff, surgeons, nursing staff, trauma coordinators, and administrators. The participants were purposefully selected with multiple sources of data being collected with both photo-solicitation and photo-elicitation to bring deeper meaning to the interpretation of the data. This qualitative study collected participants’ descriptions of their perspectives utilizing the photographs each individual took of their work environment. These photographs were the catalyst for interviews to answer the research questions. The photographs and interview comments were then analyzed and coded to identify similarities and differences among the participants. The photographs were first sorted to determine the number of pictures that were of the same areas and which pictures were the outliers of lone environmental factors. Each of the photos and the participant responses were coded and clustered to identify areas of focus. From these areas of focus, themes environment on team efficiencies, the connections to the literature, and expansion of the current body of knowledge of the organizational effects. The themes that emerged from this photo elicitation were rich descriptions of physical elements identifying positive environmental effects on teamwork within the trauma team. The themes that emerged from the photographs and interviews, including multi-agency teamwork, resuscitation room design, elevator and hallways, signage, patient rooms, equipment and supply rooms, communication, and roles and responsibilities, have shown that the physical environment has been deliberately built with teamwork as the main premise.
Covers not scanned.
Keywords: Health care teams -- Case studies; Teams in the workplace -- Case studies; Affect (Psychology) -- Case studies; Intensive care units -- Case studies; Surgical intensive care -- Case studies; Trauma centers -- Case studies